Elite plant metabolites extend the shelf life and quality of banana at room temperature - Divyabharathi, G; Krishna, K Rama; Chithra , M (Journal of Postharvest Technology, 2023)
India is the world’s largest producer of banana. Even though it has limited export because of its short shelf life and chemical residues. This has led to search of alternate ways, which do not leave any chemical residues harming human health as well as prolong the shelf life of banana. Polyamine-elite plant metabolites, have been attempted to increase the shelf life of fruits. But minuscule research findings on banana shelf life extension are reported. A study was conducted to investigate the efficiency of exogeneous application of polyamines on banana cv. ‘Karpooravalli’ (ABB). Banana fruit are treated with different concentrations of (10, 20, 30mg), putrescine, spermidine, spermine and stored at ambient conditions (32±1°C and 65±3% RH). The result showed that 20mg putrescine was more efficient than other treatments. Putrescine (20mg) application lowers the physiological loss of weight (10.79%), lowers ripening rate (1.39%), maintain a lower level TSS (16.5°B), reduced spoilage with higher consumer acceptance and extend the shelf life for seven days. Spermidine 20mg was found as the second-best treatment which showed 6 days of extension of shelf life. Untreated fruit exhibits higher physiological weight loss, TSS, spoilage, ripening rate with a shelf life of only 4 days. Finally, the results proven that polyamine application lowers loss of weight and delay the ripening rate thereby increasing shelf life.